Sequential high-dose treatment with peripheral blood progenitor cell transplantation in patients with multiple myeloma - Goldschmidt, Hartmut; Hegenbart, Ute; Moos, Marion; Engenhart, Rita; Haas, Rainer; Hunstein, Werner; Wannenmacher, Michael (Stem cells, 1995)
In June 1992, we started a dose-escalated cytotoxic therapy with peripheral blood progenitor cell (PBPC) transplantation in patients with chemosensitive multiple myeloma (MM). At the time of best response to conventional treatment, 70 patients received high-dose cyclophosphamide (HD-CY) or, in case of pre-existing heart disease, dose-escalated ifosfamide/mitoxantrone followed by filgrastim (R-metHuG-CSF, 300 μg/day). PBPC collection was commenced when CD34+ cells were detectable using direct immunofluorescence analysis. Fifty-four out of 70 patients were successfully harvested ( 2.5 x 106 CD34+ cells/kg body weight [BW]) after the first cycle of HD chemotherapy. Conditioning therapy consisted of 140 mg/m2 melphalan plus TBI (14.4 Gy hyperfractionated) or 200 mg/m2 melphalan in patients not eligible for TBI because of previous radiotherapy. To date, 56 patients have been transplanted. Autografts contained a median of 3.4 x 106 CD34+ cells/kg BW. Following reinfusion of PBPC, rapid engraftment was achieved in 54 out of 56 patients with a median of 14 days (range 9-23) to reach 0.5 x 109/l neutrophils and 10 days (range 5-22) for an unsubstituted platelet count of > 20 x 109/l. One patient died of transplantation-related complications. Sequential HD treatment improved the remission status (European Bone Marrow Transplantation criteria) in 19 out of 46 patients (9 patients too early). Of note, in 11 patients the immunofixation became negative and a polyclonal immunoglobulin reconstitution was achieved. Our protocol provides an effective treatment strategy for patients with advanced MM combined with low treatment-related toxicity.